1998
DOI: 10.1002/hep.510270410
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by dexamethasone of transforming growth factor β1,-induced apoptosis in rat hepatoma cells: A possible association with Bcl-xL induction

Abstract: The authors previously reported that transforming growth factor beta1 (TGF-beta1) induces apoptosis in McA-RH7777 (7777) and McA-RH8994 (8994) rat hepatoma cell lines. Although these cell lines exhibit different responses to glucocorticoid treatment in various cellular functions and gene expression, dexamethasone (DEX) inhibited spontaneous and TGF-beta1-induced apoptosis in both. Analysis of analogous hormones in TGF-beta1-induced apoptosis in 8994 cells suggested the inhibitory effect to be glucocorticoid-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 47 publications
1
70
1
Order By: Relevance
“…These reductions were explained by a greater programmed cell death in the foci than in surrounding hepatocytes. Because the changes of pro-and antiapoptotic proteins induced by IFN-␣2b were similar to those attributed to TGF-␤ 1 , 14,15,19 we studied the possibility that TGF-␤ 1 could be involved in the programmed cell death induced by IFN-␣2b. Thus, the present work determines for the first time that endogenous TGF-␤ 1 is implicated in the increased apoptosis on the foci of IFN␣2b-treated rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reductions were explained by a greater programmed cell death in the foci than in surrounding hepatocytes. Because the changes of pro-and antiapoptotic proteins induced by IFN-␣2b were similar to those attributed to TGF-␤ 1 , 14,15,19 we studied the possibility that TGF-␤ 1 could be involved in the programmed cell death induced by IFN-␣2b. Thus, the present work determines for the first time that endogenous TGF-␤ 1 is implicated in the increased apoptosis on the foci of IFN␣2b-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, the involvement of Bcl-2, Bax, and Bcl-x L proteins in TGF-␤ 1 -induced apoptosis has not been completely established. TGF-␤ 1 decreased the antiapoptotic protein Bcl-x L in diverse hepatoma cell lines, 14,15 whereas in other hepatoma cells no changes in Bax or Bcl-x L were observed. 18 On the other hand, overexpression of Bcl-2 blocked induction of apoptosis by TGF-␤ 1 in human hepatoma cells.…”
mentioning
confidence: 88%
“…14 ± 16 Although glucocorticoids induce rapid apoptosis in susceptible thymocyte and lymphocyte populations, several studies have demonstrated the inhibitory effects of glucocorticoids against apoptosis in various models: (i) DEX inhibits spontaneous as well as TNF-a-induced human neutrophil apoptosis, 17 ± 19 (ii) DEX and hydrocortisone abolish tumour necrosis factor a (TNFa)-induced cytoxicity of several tumour cell lines via inhibition of phospholipase A 2 activity, 20,21 and (iii) DEX inhibits spontaneous apoptosis and transforming growth factor b 1 -induced apoptosis in rat hepatoma cells via Bcl-xL induction. 22,23 However, there appears to be a dual role of glucocorticoids in the regulation of cell death although the mechanism of the anti-apoptotic effects of glucocorticoids has rarely been investigated.…”
Section: Apoptosismentioning
confidence: 99%
“…5 Furthermore, DEX has been shown to either inhibit apoptosis in some cells such as human neutrophils, 6 tumor cells, 7 and primary human and rat hepatocytes 8 or induce apoptosis in others including thymocytes and lymphocytes. 9,10 The antiapoptotic effect by DEX is regulated by several sets of genes, the best characterized of which are the Bcl-2 family such as Bcl-2 and Bcl-xL, which prevent spontaneous apoptosis of cultured primary hepatocytes.…”
Section: Introductionmentioning
confidence: 99%